Обзор социологической литературы по проблемам аграрного реформирования и социального развития деревни - Шатохин, А. (Социология: теория, методы, маркетинг, 2000)
The main stages and problems of agrarian reform and social development of countryside which have been discussed in sociological literature are analyzed in the article. In 1960–1980-ies, a special attention was paid to systematic investigation of the trends of social development of rural regions of the USSR from the point of view of social consequences of the technological revolution, social factors regulating labor behavior, social and demographic structure of the rural population, etc. In 1990-ies, sociologists were studying mainly such points as general conception and the course of agrarian reforms in the countries of the former Soviet Union, macro-structural priorities, formation of private sector in agriculture, social consequences of the market transformation in the countryside, etc.